Chimeric antigen receptor (CAR) T cells targeting a pathogenic MHC class II:peptide complex modulate the progression of autoimmune diabetes. (January 2019) - Zhang, Li; Sosinowski, Tomasz; Cox, Aaron R.; Cepeda, Joseph Ray; Sekhar, Nitin S.; Hartig, Sean M.; Miao, Dongmei; Yu, Liping; Pietropaolo, Massimo; Davidson, Howard W.
Abstract: A primary initiating epitope in the NOD mouse model of Type 1 Diabetes (T1D) lies between residues 9 and 23 of the insulin B chain. The B:9-23 peptide can bind to the NOD MHC class II molecule (I-A g7 ) in multiple registers, but only one, (register 3, R3), creates complexes able to stimulate the majority of pathogenic B:9-23-specific CD4 + T cells. Previously we generated a monoclonal antibody (mAb287) that targets this critical I-A g7 -B:9-23(R3) complex. When given weekly to pre-diabetic mice at either early or late stages of disease, mAb287 was able to delay or prevent T1D in the treated animals. Although the precise mechanism of action of mAb287 remains unclear, we hypothesized that it may involve deletion of antigen presenting cells (APCs) bearing the pathogenic IA g7 -B:9-23(R3) complexes, and that this process might be rendered more efficient by re-directing cytotoxic T cells using a mAb287 chimeric antigen receptor (287-CAR). As anticipated, 287-CAR T cells secreted IFN-γ in response to stimulation by I-A g7 -B:9-23(R3) complexes expressed on artificial APCs, but not I-A g7 loaded with other peptides, and killed the presenting cells in vitro. A single infusion of 287-CAR CD8 + T cells to young (5 week old) NOD mice significantly delayed the onset of overt hyperglycemia compared to untreated animals ( p = 0.022). None of the 287-CAR CD8 + T cell treated mice developed diabetes before 18 weeks of age, while 29% of control-CAR T cell treated mice ( p = 0.044) and 52% of the un-treated mice ( p = 0.0001) had developed T1D by this time. However, the protection provided by 287-CAR CD8 + T cells declined with time, and no significant difference in overall incidence by 30 weeks between the 3 groups was observed. Mechanistic studies indicated that the adoptively transferred 287-CAR T cells selectively homed to pancreatic lymph nodes, and in some animals could persist for at least 1–2 weeks post-transfer, but were essentially undetectable 10–15 weeks later. Our study demonstrates that CAR T cells specific for a pathogenic MHC class II:peptide complex can be effective in vivo, but that a single infusion of the current iteration can only delay, but not prevent, the development of T1D. Future studies should therefore be directed towards optimizing strategies designed to improve the longevity of the transferred cells. Highlights: Anti-[I-A g7 /insulin B:9-23 (register 3)] redirected CD8 T cells kill APCs expressing their target antigens. The re-directed T cells selectively accumulate in organs where their target ligands are presented. A single infusion of these CAR T cells suppresses the formation of insulin autoantibodies and delays T1D in young NOD mice.